Kritik Sosial pada Puisi Lagu Orang Usiran Karya W. H. Auden: Social criticism on poetry “Lagu Orang Usiran” by W. H. Auden - Hudhana, Winda Dwi; Guci, Aldo Ferdianda; Wiharja, Irpa Anggriani; Fitriani, Hamdah Siti Hamsanah (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
This research aims to determine social criticism in the poem Lagu Orang Usiran by W. H. Auden. This research is qualitative research. The data used are sentences in the poem Lagu Orang Usiran which contain social criticism. The data source for this research is the poem Lagu Orang Usiran by W. H, Auden. The data collection technique in this research is reading and note-taking techniques. Data analysis techniques use data reduction techniques, data presentation and drawing conclusions. The research results found that the social criticism in the poem Lagu Orang Usiran by W. H. Auden is social inequality, social conflict, nepotism, corruption, tyranny, social awareness and social mobility. In this poem the author wants to describe the reality of people's lives who struggle to live in the harshness of life in big cities. This poem criticizes the arbitrary actions carried out by the ruler who founded his ruling dynasty through nepotism. The condition of society has become differentiated due to social stratification factors and rampant corruption, resulting in the state and people becoming increasingly miserable.